The Association Between Serum/Plasma Leptin Levels and Obstructive Sleep Apnea Syndrome: A Meta-Analysis and Meta-Regression - Li, Xiaoyan; He, Jie (Frontiers in Endocrinology, 2021)
Background: Obstructive sleep apnea syndrome (OSAS) is associated with various adipokines. Leptin, a common adipokine, has attracted considerable attention of many researchers in recent years. So far, there has been little agreement on whether blood leptin levels differ in patients with OSAS. Thus, this meta-analysis examined the relationship between serum/plasma leptin levels and the occurrence of OSAS. Method: WanFang, Embase, CNKI, Medline, SinoMed, Web of Science, and PubMed were searched for articles before March 30, 2021, with no language limitations. STATA version 11.0 and R software version 3.6.1 were used to analyze the obtained data. The weighted mean difference and correlation coefficients were used as the main effect sizes with a random-effects model and a fixed-effects model, respectively. Trial sequential analysis was conducted using dedicated software. Result: Screening of 34 publications identified 45 studies that met the inclusion criteria of this meta-analysis and meta-regression. Our results suggested that plasma/serum leptin levels were remarkably higher in individuals with OSAS than in healthy individuals. Subgroup analyses were performed based on OSAS severity, ethnicity, age, body mass index, assay type, and sample source. The serum and plasma leptin levels were increased in nearly all OSAS subgroups compared to those in the corresponding control groups.. Meta-regression analysis indicated that age, BMI, severity, assay approaches, study design, PSG type and ethnicity did not have independent effect on leptin levels . Furthermore, a positive relationship between the serum/plasma leptin level and apnea-hypopnea index (AHI) was found in the meta-analysis. The results of the trial sequential analysis suggested that the enrolled studies surpassed the required information size, confirming that our study findings were reliable. Conclusion: Our study results demonstrate that OSAS patients have higher leptin levels in serum/plasma compared to controls, and the serum/plasma leptin level is positively correlated with AHI, especially in adults.